2013
DOI: 10.1124/jpet.113.208421
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Profiling of Phosphoinositide 3-Kinase Inhibitors as Mitigators of Ionizing Radiation–Induced Cell Death

Abstract: Ionizing radiation (IR) induces genotoxic stress that triggers adaptive cellular responses, such as activation of the phosphoinositide 3-kinase (PI3K)/Akt signaling cascade. Pluripotent cells are the most important population affected by IR because they are required for cellular replenishment. Despite the clear danger to large population centers, we still lack safe and effective therapies to abrogate the life-threatening effects of any accidental or intentional IR exposure. Therefore, we computationally analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…9, 16 Interestingly, most of the PI3K inhibitors with radiation mitigative effects also inhibit mTOR, which is a master regulator of cell growth and metabolism and points to a potential role for mTOR in mitigating the effects of IR in NCCIT cells. This hypothesis was supported with the identification of rapamycin in the current screen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9, 16 Interestingly, most of the PI3K inhibitors with radiation mitigative effects also inhibit mTOR, which is a master regulator of cell growth and metabolism and points to a potential role for mTOR in mitigating the effects of IR in NCCIT cells. This hypothesis was supported with the identification of rapamycin in the current screen.…”
Section: Resultsmentioning
confidence: 99%
“…9, 16 Our previously described caspase 3/7 assay 9, 16 was adapted to an automated screening format. Briefly, we seeded 3500 NCCIT cells/well in 384 well microtiter plates after 0 or 4 Gy IR using a JL Shepard Mark I Model 68 cesium source (75 cGy/min).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of PI3K inhibitor treatments on cell cycle status following c-irradiation were studied, and it was found that both LY294002 and PX-867 treatments in vitro of human pluripotent embryonal carcinoma cells reduced the proportion of cells in S phase, while increasing the proportion of cells in G1. Similarly, treatments with LY294002 and PX-867 after irradiation also enhanced the G2 population as well as the G1 population, while decreasing the fraction of cells in S phase while increasing the extent of DNA damage as assessed by c-H2AX (Lazo et al 2013). Although quite interesting, these observations clearly suggest the need for more rational drug design based on specific pharmacological 'targeting' for radiomitigation purposes.…”
Section: Phosphoinisitide-3 Kinase (Pi3k) Inhibitor: Ly294002mentioning
confidence: 84%
“…Single doses of LY294002 (CID3973) or PX-867 (CID24798773), PI3K inhibitors (30 mg/kg, ip), administered as injury-mitigators 4 h after 9.25 Gy c-irradiation, significantly increased survival in C57BL/6NTac female mice (Lazo et al 2013). In another study, LY294002 enhanced C57BL/6NTac female mice survival when administered ip at a dose of 30 mg/kg at 10 min, 4 h, or 24 h after 9.25 Gy TBI (Zellefrow et al 2012).…”
Section: Phosphoinisitide-3 Kinase (Pi3k) Inhibitor: Ly294002mentioning
confidence: 99%
“…Ionizing radiation induces genotoxic stress that triggers adaptive cellular responses, such as activation of the phosphoinisitide-3 kinase (PI3K)/Akt signaling cascade. A single dose of LY294002 (CID3973) or PX-867 (CID24798773) administered after a lethal dose of γ-irradiation significantly enhanced mouse survival [ 149 ]. Cell cycle checkpoints are important regulators of cell survival after radiation exposure; cell cycles after γ-irradiation and PI3K inhibitor treatment was investigated [ 149 ].…”
Section: Discussion Of Selected Radiation Countermeasures Under Dementioning
confidence: 99%